Prior exposure to B. pertussis shapes the mucosal antibody response to acellular pertussis booster vaccination - van Schuppen, Evi; Fröberg, Janeri; Venkatasubramanian, Prashanna Balaji; Versteegen, Pauline; de Graaf, Hans; Holubová, Jana; Gillard, Joshua; van Gageldonk, Pieter G M; Joosten, Irma; de Groot, Ronald; Šebo, Peter; Berbers, Guy A M; et al. (Nature communications, 2022)
Bordetella pertussis (Bp), the causative agent of pertussis, continues to circulate despite widespread vaccination programs. An important question is whether and how (sub)clinical infections shape immune memory to Bp, particularly in populations primed with acellular pertussis vaccines (aP). Here, we examine the prevalence of mucosal antibodies against non-vaccine antigens in aP-primed children and adolescents of the BERT study (NCT03697798), using antibody binding to a Bp mutant strain lacking aP antigens (Bp_mut). Our study identifies increased levels of mucosal IgG and IgA binding to Bp_mut in older aP-primed individuals, suggesting different Bp exposure between aP-primed birth cohorts, in line with pertussis disease incidence data. To examine whether Bp exposure influences vaccination responses, we measured mucosal antibody responses to aP booster vaccination as a secondary study outcome. Although booster vaccination induces significant increases in mucosal antibodies to Bp in both cohorts, the older age group that had higher baseline antibodies to Bp_ mut shows increased persistence of antibodies after vaccination.
Keywords: Antibody Formation; Antigens, Bacterial; vakcinace; Humans; dítě; Vaccination; Child; antigeny bakteriální; lidé; Bordetella pertussis; pertuse; sekundární imunizace; Immunization, Secondary; protilátky; Adolescent; tvorba protilátek; Antibodies; Whooping Cough; mladiství